Theory of double ionization of a neighboring molecule by interatomic Coulombic decay - Fedyk, Jacqueline; Gokhberg, Kirill; Cederbaum, Lorenz S. (Physical review, 2021)
Several known processes, such as single-photon double ionization and double Auger decay, result in correlated emission of two electrons from an atom or molecule. The ratio of double to single ionization in these processes usually amounts only to several percent. Recently, an experiment was reported in helium droplets doped with alkali dimers, where double ionization of the dimer after excitation of the helium proceeds via interatomic Coulombic decay and occurs with an efficiency comparable to that of single ionization via the usual interatomic Coulombic decay. Motivated by these experimental results, we investigate here the theory of this double interatomic Coulombic decay (dICD) process. First, we develop an explicit asymptotic formula for the decay width of dICD based on the assumption that the electronically excited system providing the necessary excess energy and its neighbor are spatially well separated. This formula contains only quantities accessible experimentally for the separated entities - the system and its neighbor. Second, we derive a general analytical expression for the decay width of dICD by using many-body perturbation theory. Finally, we investigated the efficiency of dICD for experimentally realizable small atomic and molecular clusters employing the asymptotic formula.
Gesehen am 26.03.2021